No Change in Southern Ocean Circulation in the Indian Ocean From the Eocene Through Late Oligocene. Issue 2 (5th February 2018) - Wright, Nicky M.; Scher, Howie D.; Seton, Maria; Huck, Claire E.; Duggan, Brian D.
Abstract: Deciphering the evolution of Southern Ocean circulation during the Eocene and Oligocene has important implications for understanding the development of the Antarctic Circumpolar Current and transition to Earth's "icehouse" climate. To better understand ocean circulation patterns in the Indian Ocean sector of the Southern Ocean, we generated a new fossil fish tooth neodymium isotope record ( ε Nd ) from the upper Eocene to upper Oligocene sections (36–23 Ma) of Ocean Drilling Program Sites 744 and 748 (Kerguelen Plateau, Indian Ocean). Reconstructed seawater ε Nd values from fossil fish teeth are used to trace changes in water masses across ocean basins. The records from Site 748 and Site 744 reveal a gradual shift from ε Nd values around −6.5 to −7.5 in the late Eocene to ε Nd values between −7.5 and −8.3 by the late Oligocene, consistent with a Circumpolar Deep Water (CDW) influence at the Kerguelen Plateau throughout the Oligocene. We interpret the shift to less radiogenic values to reflect the increased export of Northern Component Water to the Southern Ocean, likely into the proto‐CDW. However, the records show no major change in water mass composition around the Kerguelen Plateau that would accompany an increase in Pacific throughflow related to the opening of Drake Passage and imply that Pacific throughflow via the Drake Passage occurred by the late Eocene. High‐frequency variability in ɛ Nd values at Site 744 is interpreted as an imprint of Oligocene glacial activity, with a particularly pronounced excursion at 32.6 Ma roughly coinciding with other glacial weathering indicators around Antarctica. Key Points: Long‐term decrease in neodymium isotope ratios from fossil fish teeth reflects increased export of northern component water to proto‐CDW Record from ODP Site 744 suggests a local response to glacial weathering of Antarctica Neodymium isotope ratios from Kerguelen Plateau show no change in water mass mixing related to the Drake Passage